An Efficient Approximation Method for Calculating Confidence Level of Negative Survey. (27th September 2015) - Liu, Ran; Peng, Jinghui; Tang, Shanyu
Abstract : The confidence level of negative survey is one of the key scientific problems. The present work uses generation function to analyse the confidence level and uses a greedy algorithm to calculate that, which is used to evaluate the dependable level of negative survey. However, the present method is of low efficiency and complex. This study focuses on an efficient approximation method for calculating the confidence level of negative survey. This approximation method based on central limit theorem and Bayesian method can get the results efficiently.